Effectiveness of Information Services to Improve Students' Understanding of Reproductive Health in Grade IX of Smp Negeri 6 Klaten - Ratna Pratiwi; Wangid, Muhammad Nur (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aims to determine the effectiveness of information services in improving the understanding of reproductive health of grade IX students at SMP Negeri 6 Klaten. The background of this study is based on the low understanding of adolescents on reproductive issues, which can have an impact on increasing the risk of risky sexual behavior, unwanted pregnancy, and drug abuse. The study used the Classroom Action Research (CAR) method which was carried out in two cycles, each consisting of four information service meetings. The subjects of the study were 31 grade IX students. Data collection techniques used observation, interviews, documentation, and questionnaires. The results showed that the average score of student understanding increased from 66, 60% (moderate category) in the pretest to 78.25 % (high category) in the posttest. The increase occurred in all indicators, with the highest increase in the indicator of understanding sexually transmitted diseases. These findings indicate that information services are effective as an educational strategy in equipping adolescents with healthy knowledge and attitudes towards reproductive issues. Therefore, information services can be used as a preventive approach in reproductive health education in schools.